Cyber Risk Assessment Principles for Modern Digital Museums - Todorov, Todor; Lutfiu, Shpend (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2022)
Modern museums as well as other sectors that have their activity exposed to the internet process digital data. The digitalization of museums and other institutions that promote cultural heritage has gained momentum in recent years, especially during the COVID-19 pandemic, when their activities were completely closed to the public. Cybersecurity is based on preventive methods applied to maintain the confidentiality, integrity and availability of digital data and services provided. In the paper is presented an analysis of the principles and standards for the risk management of modern digital museums. The paper analyses the principles risk management and compliance requirements needed to assess the risk of modern digital museums, based on which institutions dealing with cultural heritage will be able to decide on the investments necessary for protection of their technologies and services they provide.
Keywords: Digital Data; Cyber Security; Risk Assessment; Modern Museums